Communicative Behavior Of The Person As An Object Of Self-Research Of Psychologists - Raimdjanov Mirkarim Talibjanugli (Euro Asian Journal Publishing, 2024)
In psychological research, problems of human behavior are analyzed from various theoretical and practical points of view. The nature of behavior, the reasons for its origin and consequences, the possibilities of explanation, regulation and change have been interpreted by scientists in different ways. In the scientific article, the researches conducted on the communicative behavior of the person are theoretically fully covered, in addition, special attention is paid to the importance of the family environment in the formation of behavior
Keywords: behavior; behaviorfamily environment; upbringing; morality